Black Hole Sign on Noncontrast Computed Tomography in Predicting Hematoma Expansion in Patients with Intracerebral Hemorrhage: A Meta-analysis - Chen, Yilin; Tian, Lu; Wang, Longlun; Qin, Yong; Cai, Jinhua (Current Medical Imaging, 2020)
Background: Black hole sign represents a novel imaging marker for predicting hematoma expansion (HE) in patients with intracerebral hemorrhage (ICH). Several previous studies have reported the accuracy of black hole sign in predicting HE, but the accuracy was variable. We performed a meta-analysis to systematically assess the accuracy of black hole sign in predicting HE in patients with ICH. Methods: A systematic search was performed to identify relevant English and Chinese articles (from inception to January 2019). All studies on the accuracy of black hole sign in predicting HE in patients with ICH were included. Pooled sensitivity, specificity, and positive and negative likelihood ratios were calculated. Pooling was conducted using the bivariate generalized linear mixed model. Forest plots and a summary receiver operator characteristic plot were generated. We used I² to test heterogeneity and investigated the source of heterogeneity by meta-regression. Publication bias was assessed by Deeks’ funnel plot asymmetry test. Results: A total of 6 studies with 1876 patients were included in this meta-analysis. The pooled sensitivity, specificity, and positive and negative likelihood ratios of black hole sign for predicting HE were 0.30, 0.93, 4.00 and 0.75, respectively. The area under the curve (AUC) was 0.83. The studies had substantial heterogeneity (I²=89.00%, 95% CI 78.00-100.00). Low risk of publication bias was detected. Conclusion: Black hole sign is a useful imaging marker with high specificity in predicting hematoma expansion in patients with intracerebral hemorrhage.
Keywords: contrast computed tomography